Identifying Actionable Variants in Cancer - The Dual Web and Batch Processing Tool MTB - Report...Joint Conference of the 67th Annual Meeting of the German Association of Medical Informatics, Biometry, and Epidemiology e.V. (gmds) and the 14th Annual Meeting of the TMF - Technology, Methods, and Infrastructure for Networked Medical Research, May 2022, Kiel, Germany (Virtual). - KURZ, Nadine S.; PERERA-BEL, Júlia; HÖLTERMANN, Charlotte; TUCHOLSKI, Tim; YANG, Jingyu; BEISSBARTH, Tim; DÖNITZ, Jürgen (Studies in Health Technology & Informatics, 2022)
Next-generation sequencing methods continuously provide clinicians and researchers in precision oncology with growing numbers of genomic variants found in cancer. However, manually interpreting the list of variants to identify reliable targets is an inefficient and cumbersome process that does not scale with the increasing number of cases. Support by computer systems is needed for the analysis of large scale experiments and clinical studies to identify new targets and therapies, and user-friendly applications are needed in molecular tumor boards to support clinicians in their decision-making processes. The MTB-Report tool annotates, filters and sorts genetic variants with information from public databases, providing evidence on actionable variants in both scenarios. A web interface supports medical doctors in the tumor board, and a command line mode allows batch processing of large datasets. The MTB-Report tool is available as an R implementation as well as a Docker image to provide a tool that runs out-of-the-box. Moreover, containerization ensures a stable application that delivers reproducible results over time. A public version of the web interface is available at: http://mtb.bioinf.med.unigoettingen. de/mtb-report